TURN-TAKING IN CLASS SEMINAR DISCUSSION - Lidya, Marina; Melvina, Melvina (Universitas PGRI Sumatera Barat, 2019)
This research investigated the process of turn-taking in an Indonesian classroom context. It investigated the class seminar discussions of second-year graduate students at language education section, Graduate Program of Faculty of education of Riau University. The aims of this research were to examine the major factors that influence the process of turn-taking in-class seminar discussion, the types of turn-taking emerged from the factors, and the implications of the turn-taking emerged to the atmosphere and the process of learning. As research on classroom discourse, the research was designed as qualitative research. The data were collected through observation of passive participation and structured interview. The model of Miles and Huberman was used to analyze the data. The findings show that there were three major factors that have influenced the process of turn-taking in-class seminar discussion. The factors were the models of discussion applied, the role of the moderator and the direct reward. Each factor implied the process of turn-taking in-class seminar discussion. The types of turn-taking emerged from the application of the factors implied the atmosphere and the process of learning.